Monitoring of ground water quality and heavy metals in soil during large scale bioremediation of petroleum hydrocarbon contaminated waste in India: case studies - Ajoy Kumar Mandal; Atanu Jana; Abhijit Datta; Priyangshu M. Sarma; Banwari Lal; Jayati Datta (Journal of Natural Resources and Development, 2014)
Bioremediation using microbes has been well accepted as an environmentally friendly and economical treatment method for disposal of hazardous petroleum hydrocarbon contaminated waste (oily waste) and this type of bioremediation has been successfully conducted in laboratory and on a pilot scale in various countries, including India. Presently there are no federal regulatory guidelines available in India for carrying out field-scale bioremediation of oily waste using microbes. The results of the present study describe the analysis of ground water quality as well as selected heavy metals in oily waste in some of the large-scale field case studies on bioremediation of oily waste (solid waste) carried out at various oil installations in India. The results show that there was no contribution of oil and grease and selected heavy metals to the ground water in the nearby area due to adoption of this bioremediation process. The results further reveal that there were no changes in pH and EC of the groundwater due to bioremediation. In almost all cases the selected heavy metals in residual oily waste were within the permissible limits as per Schedule – II of Hazardous Waste Management, Handling and Transboundary Movement Act, Amendment 2008, (HWM Act 2008), by the Ministry of Environment and Forests (MoEF), Government of India (GoI).